Veterinary comparative hematopathology - Valli, Victor E. (Blackwell Pub., 2007)
The book offers a unique comparative approach based on the WHO classification of these tumors in humans. Known animal tumors are described and compared to their counterparts in humans. Those tumors now defined in humans but without a recognized animal counterpart are described in the human context, thus better facilitating future identification in animals.